Embracing Joy: A Behavioural Paradigm Shift in Addressing Psychological Health Through Laughter Yoga Among Special Orphan Children of Delhi, India - Sharma, Anchal (Journal of Neonatal Surgery, 2025)
Background: Laughter yoga, a unique fusion of playful laughter exercises and deep breathing techniques, offers a holistic and innovative approach to mental health. This study examines the transformative impact of laughter yoga on stress, anxiety, and depression among special orphan children in Delhi who often experience significant emotional and psychological challenges. Objectives: The primary objective of this study is to evaluate the effectiveness of laughter yoga in reducing stress in special orphan children. Additionally, the study aims to explore whether laughter yoga can induce a behavioural paradigm shift towards improved mental health and overall well-being in this vulnerable population. Methods: We employed a two-group experimental design involving 30 having, 15 in each group (15 Boys, 15 girls), orphan special children aged 8-16 years, each with various disabilities, including visual, hearing, and locomotor impairments. These children participated in a structured laughter yoga program for three months, attending sessions five days a week. Assessments were conducted at five different time points: baseline (before starting the program), 3 weeks, 6 weeks, 9 weeks, and 12 weeks. We used the Depression Anxiety Stress Scales - Youth Version (DASS-21) to measure levels of stress, anxiety, and depression at each time point. Results: Statistical analysis using paired sample t-test revealed significant and continuous reductions in depression, anxiety and stress levels among the participants over the course of the intervention (p < 0.05). These findings highlight the profound positive impact of laughter yoga on the mental health of the special orphan children involved in the study. Conclusions: The study's findings suggest that laughter yoga is a highly effective psychosocial intervention for reducing psychological distress and enhancing emotional resilience in orphan children with special needs. By integrating joy and mindfulness, laughter yoga promotes a holistic approach to mental health and well-being, significantly contributing to this vulnerable population's overall quality of life.